Optogenetic stimulation of Kiss1ARC terminals in the AVPV induces surge-like luteinizing hormone secretion via glutamate release in mice - Shen, Xi; Liu, Yali; Li, Xiao Feng; Long, Hui; Wang, Li; Lyu, Qifeng; Kuang, Yanping; O’Byrne, Kevin T. (Frontiers in Endocrinology, 2022)
Kisspeptin neurons are mainly located in the arcuate (Kiss1ARC, vis-à-vis the GnRH pulse generator) and anteroventral periventricular nucleus (Kiss1AVPV, vis-à-vis the GnRH surge generator). Kiss1ARC send fibre projections that connect with Kiss1AVPV somata. However, studies focused on the role of Kiss1ARC neurons in the LH surge are limited, and the role of Kiss1ARC projections to AVPV (Kiss1ARC→AVPV) in the preovulatory LH surge is still unknown. To investigate its function, this study used optogenetics to selectively stimulate Kiss1ARC→AVPV and measured changes in circulating LH levels. Kiss1ARC in Kiss1-Cre-tdTomato mice were virally infected to express channelrhodopsin-2 proteins, and optical stimulation was applied selectively via a fibre optic cannula in the AVPV. Sustained 20 Hz optical stimulation of Kiss1ARC→AVPV from 15:30 to 16:30 h on proestrus effectively induced an immediate increase in LH reaching peak surge-like levels of around 8 ng/ml within 10 min, followed by a gradual decline to baseline over about 40 min. Stimulation at 10 Hz resulted in a non-significant increase in LH levels and 5 Hz stimulation had no effect in proestrous animals. The 20 Hz stimulation induced significantly higher circulating LH levels on proestrus compared with diestrus or estrus, which suggested that the effect of terminal stimulation is modulated by the sex steroid milieu. Additionally, intra-AVPV infusion of glutamate antagonists, AP5+CNQX, completely blocked the increase on LH levels induced by Kiss1ARC→AVPV terminal photostimulation in proestrous animals. These results demonstrate for the first time that optical stimulation of Kiss1ARC→AVPV induces an LH surge-like secretion via glutamatergic mechanisms. In conclusion, Kiss1ARC may participate in LH surge generation by glutamate release from terminal projections in the AVPV.